Second-generation itaconic acid: An alternative product for biorefineries?. (July 2020) - Magalhães, Antonio Irineudo; de Carvalho, Júlio Cesar; Thoms, Juliano Feliz; Souza Silva, Rafaeli; Soccol, Carlos Ricardo
Highlights: A. terreus can produce itaconic acid with complete consumption of the xylose. The yield of itaconic acid is higher when glucose is used without xylose. Acetic acid and furfural inhibit itaconic acid production in relatively low concentrations. Abstract: The ability to produce second-generation itaconic acid by Aspergillus terreus, and the inhibitory effects of hydrolysis by-products on the fermentation were evaluated by cultivation in a synthetic medium containing components usually present in a real hydrolysate broth from lignocellulosic biomasses. The results showed that A. terreus NRRL 1960 can produce itaconic acid and consume xylose completely, but the conversion is less than the fermentation using only glucose. In addition, compared to fermentation of glucose, or even xylose, the mix of both sugars resulted in a lower itaconic acid yield. In the inhibitory test, the final itaconic acid titer was reduced by acetic acid, furfural, and 5-hydroxymethylfurfural concentrations of, respectively, 188, 175, and 700 mg L −1 . However, the presence of any amount of acetic acid proved to be detrimental to itaconic acid production. This research sheds some light on doubts about the biorefinery implementation of itaconic acid production.